Electricity tariffs : the principles underlying their design and structure, with some reference to conditions in Southern Africa - Herrmann, Gerhard F. K.(Gerhard Frederick Karl) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.Comm.) -- University of Stellenbosch, 1974.